Promoting and practicing religious pluralism: Muhammadiyah experience - Biyanto Biyanto (Universitas Negeri Yogyakarta, 2020)
This article aims to discuss about the experiences of Muhammadiyah in promoting and practicing values of religious pluralism in Indonesia. As one of the biggest modern Islamic organization in the world Muhammadiyah showed to take action in promoting values of religious pluralism. It was showed by education, preaching, social welfare, inter-faith dialogue and peace, and across culture, ethnic, and religious programs. For example, Muhammadiyah formed many schools and universities at all provinces in Indonesia. The network of Muhammadiyah’s schools and universities through in districts, in fact at villages. By education, Muhammadiyah taught and practiced values of religious pluralism. It was showed, particularly, by Muhammadiyah’s schools and universities at Muslim minority provinces. Province of Papua, West Papua, and East Nusa Tenggara, for example, percentage non-Muslim students and teacher at Muhammadiyah’s schools and universities through 75%-90%. Muhammadiyah also invited non-Muslim teachers to teach religion. Muhammadiyah gave freedom for every student to practice his religious teaching. By preaching, Muhammadiyah gave an emphasis that the diversity or plurality in the human life patterns is God’s wish and a scientific fact (natural of law, sunnatullah). Therefor everyone must celebrate and respect to diversity or plurality. Until now Muhammadiyah still active inter-faith dialogue and peace with religious leaders in Indonesia, even in the world. Muhammadiyah also does programs to against terrorism. The leaders of Muhammadiyah also involved peace building programs ini the world. Promoting values of religious pluralism by Muhammadiyah is very important because Indonesia is a multicultural state in ethnic, culture, and religion.